John Gray: poet, dandy, and priest - MacCormack, Jerusha Hull (Brandeis University Press, 1991)
Klappentext: John Gray was among the "tragic generation" of English decadent artists of the 1890s and the reputed model for the hero in Oscar Wilde's novel The Picture of Dorian Gray. Though John Gray is little known today, the story of his transformation from working-class laborer to avent-garde poet to patrician priest is fascinating in its own right and serves as a window into the world of such luminaries as Wilde, W. B. Yeats, Ernest Dowson, Lionel Johnson, Arthur Symons, and Aubrey Beardsley. Jerusha McCormack's lively critical biography draws upon unpublished journals and letters, extensive interviews, and autobiographical elements in Gray's poetry and prose to tell his complete story for the first time.